BlogMiner: Web blog mining application for classification of movie reviews - (:unkn) unknown (My University, 2010)
With the increasing use of Web 2.0 platforms such as Web Blogs, discussion forums, Wikis, and various other types of social media, people began to share their experiences and opinions about products or services on the World Wide Web. Web Blogs have thus become an important source of information. In turn, great interest in blog mining has arisen, specifically due to its potential applications, such as in opinion or review search engine applications the ability to collect and analyze data. In this study, we introduce an architecture, implementation, and evaluation of a Web blog mining application, called the BlogMiner, which extracts and classifies people's opinions and emotions (or sentiment) from the contents of weblogs about movie reviews. © 2010 IEEE.
Keywords: Blog crawler; Blog mining; Opinion mining; Web blog mining